In situ observations of BrO over Antarctica - ER-2 aircraft results from 54 deg S to 72 deg S latitude - Brune, W. H.; Anderson, J. G.; Chan, K. R. (1989)
Bromine monoxide was observed in situ during nine flights of the NASA ER-2 aircraft from Punta Arenas, Chile (54 deg S latitude), to 72 deg S latitude over the Palmer Peninsula, Antarctica. The first flight for the BrO detection system was on August 28. The distribution of BrO inside the chemically perturbed region defined by greatly elevated ClO abundances was different from that found just outside. Inside, the BrO mixing ratio was 6.1 + or - 1.1 pptv above the 440 K potential temperature surface, 4.7 + or - 2.0 pptv between the 400 and 440 K surfaces, and less than 4 pptv below the 400 K surface. At high latitudes outside the chemically perturbed region, the BrO mixing ratio was 5.4 + or - 1.4 pptv near the 450 K surface, but decreased to 2.9 + or - 1.2 pptv at the 420 K surface. The abundance of BrO showed no discernible temporal trend during the course of the nine flights. Away from the south polar region, at latitudes between 47 deg S and 37 deg N and potential temperatures between 435 and 500 K (18.5- to 20.7-km altitude), the BrO mixing ratio was 0.5-3.0 pptv.